Analisis Efektifitas Pelaksanaan Pelayanan Digital Berbasis Google Form Di Suku Dinas Kesehatan Jakarta Barat - Yanti Priati; Ivan Budi Susetyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research is motivated by the results of monitoring and evaluation of the General Section and Protocol of the Mayor of the City of West Jakarta Administration regarding the use of space in the Office of the Mayor of the City of Administration of West Jakarta which mentions the lack of file storage space and the lack of digital archive documentation especially in the West Jakarta Administration City Health Sub-dept. This study aims to determine (1) the effectiveness of the implementation of archive services by digitizing storage, (2) how to use tools in performing digital archive services, (3) supporting and inhibiting factors for digital archive services by employees of the West Jakarta City Health Sub-dept. This study uses a qualitative method with administrative staff at the West Jakarta Administration City Health Sub- dept. as research subjects. Data collection on the implementation of employee digital documents was carried out through observation and interviews. The results of the study indicate that the implementation of digital documentation by employees of the West Jakarta City Administration of Health has not been effective and maximal. The author suggests: (1) campaign and network stability, (2) training and assistance related to technology-based display creation, and (3) internal policies related to digital archive storage.